A Study of the Meliaceae of India with Special Reference to West Bengal - Chaudhuri, A. B. (Indian Forester, 1965)
The Meliaceae of the Indian region are very important from the foresters point of view. Taxonomic studies on several genera were undertaken giving special attention to Aglaia, Amoora, Dysoxylum, WolJura, Chirocheton, Chukrasia, Mlelia and Azadirachta which among themselves contain more than hundred species and a check-list has been prepared. Some of the species have distinct smell to the blaze, bitter taste of the bark and leaf and distinct characteristics of bark, fruit and flower. It was found that distribution of species was mainly dependent on the rainfall and humidity and very little on rock and soil. The family has got high degree of endemism. Ceylon species and some South-Western and North-Eastern species and particularly Dysoxylum species have high degree of endemism. The study revealed that though India has land connections on all three sides the flora is high in endemics. In the Himalayas the flora has been influenced by the Japanese, Chinese, Tibetan and Malayan elements. It was found that though the Meliaceae are mainly tropical, the eastern Himalayas have several species while in the western Himalayas only one species. In the Nilgiri, Palni and Anaimalai hills no species of the Meliaceae was found above 5000'. A detailed study of the distribution and composition of the Meliaceous species in different forest types of India has been made. Analysis of the woody flora of various types of forests showed that meliaceous species form a high percentage of vegetation of both upper and middle storeys.